AB1343 EFFECTIVENESS OF A RHEUMATOLOGY EDUCATIONAL PROGRAM TO IMPROVE METHOTREXATE PRESCRIBING PRACTICES FOR RHEUMATOID ARTHRITISIN THE SOLE PUBLIC ADULT RHEUMATOLOGY CLINIC IN ETHIOPIA. (June 2019) - Hitchon, CArol; Adugna, Becky Abdissa; Demelash, Birhanu; Scuccimarri, Rosie; Colmegna, Ines; Kifle, Frehiywot; Caldron, Paul; Melkie, Addisu; Meltzer, Michele; Mengistu, Yewondwossen
Abstract : Background: Treatment of recent onset Rheumatoid Arthritis (RA) is key to preventing deformities. Initial treatment with methotrexate (MTX) is standard of care. RA treatment in resource-limited countries is complicated by competing health priorities and a lack of rheumatologists. The sole public adult rheumatology clinic in Ethiopia, is at Tikur Anbessa Specialty hospital (TASH) (Addis Ababa). Due to the lack of rheumatologists, care is provided by internists with limited rheumatology training. Objectives: To evaluate changes in RA management practice patterns following a series of educational activities provided by visiting rheumatologists. Methods: With local faculty support, visiting rheumatologists conducted educational activities at TASH between July 2016 and December 2018 (2 continuing medical education workshops; 4 clinical preceptorships lasting 2-4 weeks each). Clinical charts of a convenience sample of RA patients seen in the TASH rheumatology clinic were reviewed in September 2016 (n=48) by a team of rheumatologists and a second set in December 2018 (n=78) by an internist. Socio-demographics, arthritis features, treatment patterns and drug safety monitoring were recorded when documented. Practice patterns were compared between 2016 and 2018 using univariate statistics. Results: The patients were mainly female (90%) with a mean (standard deviation) age of 36(13) years, resided in Addis Ababa (61%) and received government funded health care (57%). When documented, (95/117; 81%) had polyarthritis and (42/55; 76%) clinical joint deformity (2016 vs 2018 p=NS). More patients were seropositive in 2016 compared to 2018 (32/43 vs 14/75 p<0.001) and more had radiographic damage (erosions, joint space narrowing, periarticular osteopenia) (21/27 vs 39/71 p<0.05). Between 2016 and 2018, prednisolone use remained common (92% in 2016 vs 99% in 2018 p=0.05) often in high doses (last visit daily dose 7.5mg (0-100) vs 5mg (0-100); p=NS; maximum daily dose 7.5 (0-100) vs 20 (0-100) p=NS) with continued documentation of steroid toxicity (45% vs 20%). The only available DMARDs prescribed were MTX (112/127; 97%) and chloroquine (50/125;40%). Median prescribed weekly MTX dose increased between 2016 and 2018 (starting dose 5 vs 7.5 mg/week p=0.01; maximum dose 7.5 vs 12.5 mg/week p<0.0001) and was co-prescribed with folate by 84% in 2016 vs 93% in 2018 (p=NS). Documentation of drug safety for those prescribed MTX improved with adequate pre-MTX labs (hematology, renal and liver panel and or hepatitis serology) requested by 46% in 2016 to 90% in 2018 (p<0.0001). When documented, MTX use was often interupted (2016 17/24; 2018 14/43 p=0.003) and mainly due to limited drug availability. Conclusion: An educational program conducted with support from the local medical community has potential to improve management of rheumatic disease in resource limited regions without adequate rheumatology capacity. However, interventions must be maintained over time and changes in practice measured to ensure that appropriate diagnosis and safe prescribing practices continue until local rheumatology expertise and capacity is available. Acknowledgement: Study funding by ILAR Disclosure of Interests: CArol Hitchon Grant/research support from: Pfizer, UCB (unrelated studies), Becky Abdissa Adugna: None declared, Birhanu Demelash: None declared, Rosie Scuccimarri: None declared, Ines Colmegna: None declared, Frehiywot Kifle : None declared, Paul Caldron: None declared, Addisu Melkie: None declared, Michele Meltzer: None declared, Yewondwossen Mengistu: None declared